2008
DOI: 10.1093/dnares/dsn020
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of Aspergillus oryzae: Learning from the History of Koji Mold and Exploration of Its Future

Abstract: At a time when the notion of microorganisms did not exist, our ancestors empirically established methods for the production of various fermentation foods: miso (bean curd seasoning) and shoyu (soy sauce), both of which have been widely used and are essential for Japanese cooking, and sake, a magical alcoholic drink consumed at a variety of ritual occasions, are typical examples. A filamentous fungus, Aspergillus oryzae, is the key organism in the production of all these traditional foods, and its solid-state c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
233
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(239 citation statements)
references
References 51 publications
1
233
0
5
Order By: Relevance
“…Operation of the sake-based CBP system at a lower solids loading (lower solid to liquid ratio) or the use of stirred or mixed fermentation vessels could possibly result in higher ethanol yields, by increasing successful enzyme-substrate interactions. Paradoxically, however, enzyme secretion has been shown to be greater on solid-state cultures as compared with highly dilute liquid cultures [27]. This could perhaps relate to a starvation response, as seen in biofilm formation.…”
Section: Ethanol (G/l)mentioning
confidence: 99%
See 2 more Smart Citations
“…Operation of the sake-based CBP system at a lower solids loading (lower solid to liquid ratio) or the use of stirred or mixed fermentation vessels could possibly result in higher ethanol yields, by increasing successful enzyme-substrate interactions. Paradoxically, however, enzyme secretion has been shown to be greater on solid-state cultures as compared with highly dilute liquid cultures [27]. This could perhaps relate to a starvation response, as seen in biofilm formation.…”
Section: Ethanol (G/l)mentioning
confidence: 99%
“…That this was not the case once again suggests that the enzyme concentration was not the rate-limiting factor in these fermentations. It has previously been reported that temperature reduction can play a role in maintaining continued expression of extracellular hydrolases when using A. oryzae in a solid-state cultivation system for the traditional manufacture of products such as soy sauce [27]. The hypothesis, which may help to explain the results observed here, is that reduced mobility of the secreted enzymes in solid-state cultures at lower temperatures may significantly reduce product feedback inhibition of the expression of hydrolases, therefore resulting in higher secreted enzyme concentrations.…”
Section: Ethanol (G/l)mentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed the homologues of nine up-regulated genes, a neutral gene (laeA), and a down-regulated gene (veA) as reported in A. nidulans (Ruger-Herreros et al 2011). In the A. nidulans study, the most up-regulated gene (ccgB) and second most up-regulated gene (ccgA) (RugerHerreros et al 2011), which are homologues of the N. crassa ccg-1 gene, a clock-controlled and glucose-repressed gene of unknown function (Arpaia et al 1995), were not found in the A. oryzae genome (Machida et al 2008). We conducted RT-PCR on nine of the 11 genes described above, excluding ccgA and ccgB.…”
Section: Resultsmentioning
confidence: 99%
“…oryzae is a fungus with high potential for the secretory production of various enzymes and is commonly used in traditional Japanese fermentation industries (Machida et al, 2008). Recently, Hossain (2013) reported the optimization of direct ethanol production using A. oryzae from non-pretreated and pre-treated corn stover in a continuous stirred batch bioreactor.…”
Section: Aspergillus Oryzaementioning
confidence: 99%